The Cardioprotective Mechanism of Phenylaminoethyl Selenides (PAESe) Against Doxorubicin-Induced Cardiotoxicity Involves Frataxin - Fu, Xiaoyu; Eggert, Mathew; Yoo, Sieun; Patel, Nikhil; Zhong, Juming; Steinke, Ian; Govindarajulu, Manoj; Turumtay, Emine Akyuz; Mouli, Shravanthi; Panizzi, Peter; Beyers, Ronald; Denney, Thomas; et al. (Frontiers in Pharmacology, 2021)
Doxorubicin (DOX) is an anthracycline cancer chemotherapeutic that exhibits cumulative dose-limiting cardiotoxicity and limits its clinical utility. DOX treatment results in the development of morbid cardiac hypertrophy that progresses to congestive heart failure and death. Recent evidence suggests that during the development of DOX mediated cardiac hypertrophy, mitochondrial energetics are severely compromised, thus priming the cardiomyocyte for failure. To help mitigate the DOX mediated development of cardiac hypertrophy, we have examined an orally active selenium based compound developed initially to treat hypertension and cardiovascular diseases, termed phenylaminoethyl selenides (PAESe). We observed that PAESe reduces DOX mediated reactive oxygen species (ROS) formation and cardiac hypertrophy in athymic mice. Mechanistically, we demonstrated that DOX impedes the stability of the iron-sulfur cluster biogenesis protein Frataxin (FXN), resulting in enhanced mitochondrial free iron accumulation, reduced aconitase activity. Further, that PAESe helped in preventing the reduction of FXN levels and the ensuing elevation of mitochondrial free iron levels. Previous studies have demonstrated that PAESe works in part, by regeneration of glutathione levels. Thus we hypothesize that PAESe can mitigate DOX mediated cardiac hypertrophy by enhancing glutathione levels and inhibiting ROS formation. Further, PAESe improves myocardial energetics, including aconitase activity, and protects against DOX-mediated attenuation of mitochondrial membrane potential (MMP). To support our hypothesis we observed by MRI analysis that PAESe significantly attenuates DOX-mediated cardiac hypertrophy. Thus in the current study we investigated the protective mechanism by PAESe against DOX mediated myocardial damage and that Frataxin is implicitly involved in DOX-mediated cardiac hypertrophy.